Development of a loop-mediated isothermal amplification (LAMP) assay for the detection of Anaplasma marginale - Giglioti, Rodrigo [UNESP]; Bassetto, Cesar Cristiano [UNESP]; Okino, Cintia Hiromi; Oliveira, Henrique Nunes de [UNESP]; Sena Oliveira, Marcia Cristina de (Springer, 2019)
Parasitemia generated by Anaplasma marginale causes significant losses in the cattle industry. A major constraint to the effective control and management of anaplasmosis in livestock is the lack of a rapid and reliable diagnostic test to identify the parasite and allow for immediate therapy. In the present study, we developed a novel DNA-based assay for the detection of A. marginale in bovine blood samples, using loop-mediated isothermal amplification (LAMP). DNA from six cattle and hemoparasite samples (Babesia bovis, Babesia bigemina, Anaplasma centrale and A. marginale) were tested for specificity, sensitivity and cross-reactions. The developed LAMP procedures were also confirmed and compared with the qPCR method. The same gene sequence (major surface protein 1b, msp1b) of A. marginale was used to design a set of primers for the LAMP and qPCR assays. The results showed that LAMP is specific, as no positive signal was observed for the other tested hemoparasites. However, the sensitivity of the qPCR assay was ten times higher than LAMP. Our findings indicate that this LAMP method has a good sensitivity and high specificity for the detection of A. marginale and may have a potential application in the detection and differentiation of bovine anaplasmosis.
Keywords: LAMP; qPCR; Anaplasma marginale; Detection; Sensibility; Specificity